2016
DOI: 10.1080/13527266.2016.1251488
|View full text |Cite
|
Sign up to set email alerts
|

Communicating CSR practices – Role of internationalization of emerging market firms

Abstract: Emerging markets suffer from institutional voids, and in such resource deficient economies, corporate social responsibility is given scant attention. However, when firms from emerging markets globalize, international stakeholders become suspicious about firms' products, services and business practices. Grounded in the liability of emergingness and legitimacy theory and using a sample of 134 manufacturing firms from one emerging market, India, this study explores how firms' international diversification intent … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
20
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(22 citation statements)
references
References 93 publications
1
20
0
1
Order By: Relevance
“…In India, studies have reported a lack of awareness of sustainability [5], and even if there is awareness, firms are not willing to pay premium prices [6]. Extensive research on CSR impacting firm performance has been carried out in developed countries but not many from an Indian perspective and mostly limited to self-reported surveys on CSR barriers [7], policies and practices towards CSR [8], the nature and characteristics of CSR. However, all these studies did not account for financial performance, especially from manufacturing firms.…”
Section: Introductionmentioning
confidence: 99%
“…In India, studies have reported a lack of awareness of sustainability [5], and even if there is awareness, firms are not willing to pay premium prices [6]. Extensive research on CSR impacting firm performance has been carried out in developed countries but not many from an Indian perspective and mostly limited to self-reported surveys on CSR barriers [7], policies and practices towards CSR [8], the nature and characteristics of CSR. However, all these studies did not account for financial performance, especially from manufacturing firms.…”
Section: Introductionmentioning
confidence: 99%
“…Highly internationalised firms may wish to perform more CSR activities not only because they attract more visibility and scrutiny from international media and other non-governmental organisations (NGOs) (Hah & Freeman, 2014) but also due to the greater amount of slack resources that may be available to them (Dahan et al, 2006) and the larger amount of risk they face if industrial accidents were to occur (Laudal, 2011). Thus, while much of the prior research in this area has focused on how internationalisation impacts CSR (Attig et al, 2016;Bondy & Starkey, 2014), ours is one of the few studies that have recently focused on the extent to which domestic CSR impacts internationalisation, especially for EMNEs (Agnihotri & Bhattacharya, 2019a;Fiaschi et al, 2017). In this context, we theoretically contribute to the institutional and strategic perspectives on CSR by suggesting that the legitimisation benefits of CSR hold not only in their domestic environments but also in expanding to foreign markets.…”
Section: Discussionmentioning
confidence: 99%
“…However, CSR implementation varies from country to country and is influenced by specific factors. Prior studies have demonstrated significant cross-national differences in the approaches taken by companies when addressing CSR-related problems, focusing particularly on the differences between developed and emerging markets (Agnihotri and Bhattacharya, 2019).…”
Section: Introductionmentioning
confidence: 99%